A fast and robust hippocampal subfields segmentation: HSF revealing lifespan volumetric dynamics - Poiret, Clement; Bouyeure, Antoine; Patil, Sandesh; Grigis, Antoine; Duchesnay, Edouard; Faillot, Matthieu; Bottlaender, Michel; Lemaitre, Frederic; Noulhiane, Marion (Frontiers in Neuroinformatics, 2023)
The hippocampal subfields, pivotal to episodic memory, are distinct both in terms of cyto- and myeloarchitectony. Studying the structure of hippocampal subfields in-vivo is crucial to understand volumetric trajectories across the lifespan, from the emergence of episodic memory during early childhood to memory impairments found in older adults. However, segmenting hippocampal subfields on conventional MRI sequences is challenging because of their small size. Furthermore, there is to date no unified segmentation protocol for the hippocampal subfields, which limits comparisons between studies. Therefore, we introduced a novel segmentation tool called HSF short for Hippocampal Segmentation Factory, which leverages an end-to-end deep learning pipeline. First, we validated HSF against currently used tools (ASHS, HIPS, and HippUnfold). Then, we used HSF on 3750 subjects from the HCP-Development, Young Adults, and Aging datasets to study the effect of age and sex on hippocampal subfields volumes. We showed a differential maturation and aging across subfields, with the Dentate Gyrus being the most affected by age. We also found faster growth and decay in men than in women for most hippocampal subfields. Our results suggest that volumetric trajectories of hippocampal subfields are nonlinear across the lifespan, which reconciles previous conflicting results. We provide a new, fast and robust, open-source tool for hippocampal subfields segmentation in MRI.